Learning and agricultural innovation in Costa Rica. The case of melon production - Barboza Arias, Luis Miguel (2018)
The document aims to analyze the institutional dimension around which different support structures for the learning and innovation management in the agricultural sector are established. The experience of melon production in Costa Rica is analyzed as a case study. Actors and their respective roles are identified through the use of the Agricultural Innovation Systems Approach (AIS). We characterized the type of linkage established between the AIS and the melon sector, considering the analysis of the objectives and strategic interactions between them. As part of the methodology, a survey to a group of 16 productive organizations and in-depth interviews with representatives of public bodies and the education sector were applied. Secondary sources of statistical information were also consulted, whose subsequent systematization was done through the technique of documentary analysis. The study concludes that the scarce provision of institutional mechanisms to include the socio-cultural dimension as part of the skills creation in farm workers affects not only sectoral competitiveness but also local development, since it does not promote the co-construction of knowledge from the participative approach. From the systemic perspective, there is a problem of institutional disarticulation that affect the quality and scope of the links. There are also conceptual deficiencies that hinder an adequate approach to innovation as an instrument of organizational development.